2021
DOI: 10.1097/md.0000000000024720
|View full text |Cite
|
Sign up to set email alerts
|

Management of outpatient with totally implantable venous access Ports during the COVID-19 epidemic

Abstract: The purpose of this study was to explore the management experience of outpatient with totally implantable central venous access Ports (TIVAPs, Ports) during the epidemic, including whether the extension of the irrigation interval will affect the incidence of catheter occlusion, the reasons for the port removal rate, and the corresponding protective treatment strategies during the COVID-19 epidemic. We retrospectively analyzed the Ports evaluation and flushing procedure data between February 3, 2020… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Finally, four studies 3,4,30,31 were included. Three researches 3,30,31 were retrospective observational studies, one research 4 was a case report. There were three articles 30,4,31 from China, and one article 3 from Korea.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, four studies 3,4,30,31 were included. Three researches 3,30,31 were retrospective observational studies, one research 4 was a case report. There were three articles 30,4,31 from China, and one article 3 from Korea.…”
Section: Resultsmentioning
confidence: 99%
“…Three researches 3,30,31 were retrospective observational studies, one research 4 was a case report. There were three articles 30,4,31 from China, and one article 3 from Korea. Flushing intervals contains more than 4 weeks, beyond 45 days, and 3-month.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are limited data on complications related to venous access during the pandemic. One recently published study analysed the effect of prolonged PORT flushing intervals during the pandemic and found no difference in occlusion rates between groups with different duration intervals [ 10 ]. However, studies that examined CRBSI incidence during the pandemic found an increase in the rates of this complication, likely due to a decrease in preventive hygiene protocols [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%